2018
DOI: 10.1080/07366299.2018.1464269
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Diglycolamide Based Solvent Extraction Processes in Spent Nuclear Fuel Reprocessing, Part 1: TODGA

Abstract: Over the last decade there has been much interest in the applications of diglycolamide (DGA) ligands for the extraction of the trivalent lanthanide and actinide ions from PUREX high active raffinates or dissolved spent nuclear fuel. Of the DGAs, the N,N,N',N'-tetraoctyldiglycolamide (TODGA) is the best known and most widely studied. A number of new actinide separation processes have been proposed based on extraction with TODGA. This review covers TODGA based processes and extraction data, specifically focusing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(81 citation statements)
references
References 60 publications
1
78
0
1
Order By: Relevance
“…Since TODGA is a neural tridentate extracting agent, which has a very strong affinity to f-elements, it can be used for a highly efficient extraction of trivalent lanthanides and minor actinides from highlevel liquid nuclear waste solutions. 5,[38][39][40] As expected, the distribution of Eu(III) ions between an aqueous 3 M HNO3 solution and an organic phase containing TODGA alone was high, i.e. 0.01 M TODGA diluted in [C4mim][Tf2N] ionic liquid or nonane yields DEu of 5.9 or 104.7, respectively ( Figure 1).…”
Section: Eu(iii) Extraction By Todga or Tbp Diluted In The Il Or Molesupporting
confidence: 72%
See 1 more Smart Citation
“…Since TODGA is a neural tridentate extracting agent, which has a very strong affinity to f-elements, it can be used for a highly efficient extraction of trivalent lanthanides and minor actinides from highlevel liquid nuclear waste solutions. 5,[38][39][40] As expected, the distribution of Eu(III) ions between an aqueous 3 M HNO3 solution and an organic phase containing TODGA alone was high, i.e. 0.01 M TODGA diluted in [C4mim][Tf2N] ionic liquid or nonane yields DEu of 5.9 or 104.7, respectively ( Figure 1).…”
Section: Eu(iii) Extraction By Todga or Tbp Diluted In The Il Or Molesupporting
confidence: 72%
“…46 For the trivalent ions, the inner coordination sphere is completed by (TODGA)x(NO3)y, where x + y = 3 and x = 2 or 3. 40 EXAFS studies of TODGA extracted Pr(III), Nd(III), Eu(III), Yb(III), and Lu(III) showed that the inner coordination sphere of these lanthanide cations saturated by the organic ligand. [Ln(L)3] 3+ species is predominant.…”
Section: Effect Of Hno3 Concentration On the Eu(iii) Extraction By Tomentioning
confidence: 99%
“…We report herein the successive solvent extraction of manganese with N,N,N',N'-tetra(n-octyl) diglycolamide (TODGA) dissolved in imidazolium-based ionic liquids. TODGA extractant has a particular affinity for trivalent metals and particularly for the rare earth elements and actinides (Whittaker et al, 2018) when used in combination with a molecular diluent such as kerosene or toluene. Several studies reported unexpected higher distribution ratio values when using this extracting molecule in combination with ILs (Panja et al, 2012), (Pan and Hussey, 2013), (Turanov et al, 2016), (Zhang et al, 2014), (Shimojo et al, 2008), (Billard, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The development and applicability of these extraction processes are limited by safety issues related to the resistance to radiation because they must work in continue operation in the recycling plant. For that reason, extractants like the diglicolamide TODGA (N,N,N 0 ,N 0 -tetraoctyldiglycolamide), which shows promising extraction properties and a good resistant to radiation, are being used widely for these applications [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%